3D printing of high solid loading zirconia feedstock via screw-based material extrusion - Lim I.Y.; Ting C.H.; Ng C.K.; Tey J.Y.; Yeo W.H.; S R.; Lee K.Y.S.; Chuah Y.D.; Teng W.D. (Elsevier Ltd, 2024)
Zirconia ceramic (3Y-TZP) feedstocks with solid loadings from 50 vol% to 68 vol%, in a 60:40 paraffin wax to LDPE ratio binder system, were prepared and printed using a screw-based material extrusion printer. A two-step debinding process involving solvent debinding (cyclohexane + ethanol) and thermal debinding (140 C600 C at 0.2 C/min) followed by sintering at 1500 C for 2 h was employed. Tests performed include TGA, density test, Vickers hardness and fracture toughness, XRD, and SEM. The TGA result showed two significant drops in weight starting at 180 C and 380 C, which corresponds to the decomposition of paraffin wax and LDPE, respectively. A minimum of 40 wt% of soluble binder was removed from the green sample after solvent immersion for 3 h at 40 C for solid loadings ?55 vol%. High solid loading feedstocks produced samples with comparable density, Vickers hardness and fracture toughness, which are 97.5%, ?12.3 GPa, and ?5.5 MPa m1/2, respectively